Fractionation methods affect the gelling properties of pea proteins in emulsion-filled gels. (April 2022) - Kornet, Remco; Sridharan, Simha; Venema, Paul; Sagis, Leonard M.C.; Nikiforidis, Constantinos V.; van der Goot, Atze Jan; Meinders, Marcel B.J.; van der Linden, Erik
Abstract: Plant proteins, after extraction from sources such as pea can be used as functional ingredients in emulsions and gels. However, the protein fractionation route used affects the protein functionality. We investigated the differences in rheological properties of emulsion-filled gel (EFGs) structured by pea protein isolate obtained using either isoelectric precipitation (PPIp) or diafiltration (PPId), at varying pH and oil content. PPIp and PPId had a protein content of 75.3 and 77.7 wt %, respectively. We first studied the oil-water interfacial rheology and composition in emulsions, as these interfacial and emulsion properties can influence EFG properties. Both PPIp and PPId formed a viscoelastic, soft-solid protein layer around the oil droplets and both PPIs were able to stabilize emulsions with monomodal droplet size between 1 and 10 μm. Additional pea protein was added to the emulsions to achieve a final protein dry matter content of 15 wt % and gelling was induced by heating the protein-enriched emulsion in the rheometer to 95 °C. At pH 5, PPIp and PPId formed EFGs with comparable firmness (i.e. similar G') and with a heterogeneous microstructure. At pH 7, PPIp formed less firm and homogeneous gels compared to PPId. The difference was related to protein solubility and aggregation, caused by different fractionation methods. In the EFGs, the presence of oil droplets did not reinforce the gel structure, which could be explained by weak interactions between the oil droplet interface and protein matrix. Our results show that pea protein fractionation routes affect the properties of PPI gels and EFGs. These insights may contribute to pea protein fractionation that is tailored to specific structural requirements for gel-based foods. Graphical abstract: Image 1 Highlights: Pea protein isolates were obtained through isoelectric precipitation (PPIp) and diafiltration (PPId). Both PPIp and PPId could stabilize emulsions with droplet sizes of 1–10 μm. In emulsion-filled gels (EFGs), an increased oil content did not increase gel stiffness. PPId former firmer, more ductile and more cohesive EFGs than PPIp. It was hypothesized that oil droplet interfaces weakly interact with the protein matrix in EFGs.